Reproductive biology of the Brazilian sharpnose shark (Rhizoprionodon lalandii) from southeastern Brazil - Motta, Fabio S. [UNESP]; Namora, Rafael C. [UNESP]; Gadig, Otto B. F. [UNESP]; Braga, F. M. S. [UNESP] (Oxford University Press, 2007)
The reproductive biology of the Brazilian sharpnose shark, Rhizoprionodon lalandii, off southeastern Brazil was investigated using data from gillnet landings. The size-at-maturity for males and females was estimated to be 59 and 62 cm total length (LT), respectively. Ovarian fecundity ranged from 3 to 7 follicles (mean = 4.S4), and uterine fecundity from 1 to S embryos (mean = 3.3). There was a slight positive relationship between female LT and the number of ovarian follicles, but uterine fecundity was not related to female LT. Embryonic growth is fast following fertilization during summer and autumn. Gestation requires 11 - 12 months, and peak parturition is between August and September. A comparison of size-at-maturity between animals from northeastern and southeastern Brazil suggests the existence of at least two stocks of R. lalandii along the Brazilian coast.
Keywords: elasmobranchii; fecundity; reproduction; shark; size-at-maturity